Heterogeneity of technology-specific R&D investments. Evidence from top R&D investors worldwide - Petros Gkotsis; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2018)
In this work, we develop and apply a methodology to estimate technology-specific R&D investments at firm level and then use these to test some arguments that have become central in the innovation literature. In particular, we first combine R&D investments with patent data of the world top R&D investors worldwide and show that investment per patent varies greatly both across technologies and across firms developing the same technology. We then use the estimated firm-technology R&D investments to assess how these are related to the international and technological strategies of firms. The estimation strategy makes use of a multilevel framework that allows us to model heterogeneity both at the firm and industry level. In particular, we show that specific firms strategies requires different level of investments and that sector specificities matter in determining R&D per patent investments, economies of scale in knowledge production, and the cost of (further) specialization. Accounting for (un)observed heterogeneity may lead to better policy design and management decisions.
Keywords: O3; O14; L10; D32; 330; patents; R&D; technology; cost; heterogeneity; internationalization